Global Rate Rises, Local Resilience: A Critical Examination of Indonesia’s Investment Dynamics Under The Fed’s Monetary Policy and Domestic Safeguards - Wardani, Kayla; Lumbanraja, Baraja; Rusdi, Ainia (LIBERATICA, 2025)
Changes in interest rate policy by the United States Federal Reserve (The Fed) have a significant impact on the economic stability of developing countries, including Indonesia. The Fed’s interest rate hike prompted global investors to withdraw funds from emerging markets and switch to US dollar assets, which could depress the rupiah exchange rate and affect capital inflows. The purpose of this study is to understand how the Federal Reserve’s interest rate policy impacts investment flows in Indonesia, with a particular emphasis on how this policy relates to Bank Indonesia’s interest rate policy and national regulations such as the Job Creation Law. The method used is a descriptive quantitative approach, with data analysis from quarterly 2016–2023. This data includes the Federal Funds rate, the BI 7 Days Reverse Repo rate, the rupiah exchange rate, and foreign capital flows consisting of foreign portfolio and foreign direct investment. The results show that portfolio investment is reduced by the Federal Reserve’s interest rate increase. On the other hand, FDI remains stable due to structural factors and Bank Indonesia’s responsive policies, which make Indonesia attractive for long-term investment.